Prenatal diagnosis of a giant intracranial teratoma associated with pulmonary hypoplasia. - Weyerts, Leah K.; Catanzarite, Val; Jones, Marilyn C.; Mendoza, Arturo (East Carolina University, 1993)
We present a case in which an intracranial tumour replacing all intracranial contents was diagnosed by sonography at 31 weeks' gestation. The patient was delivered by caesarean section and died shortly after delivery. At necropsy, the tumour was found to be a teratoma with no recognisable normal brain tissue present. Additional findings at necropsy included pulmonary and adrenal hypoplasia. The diagnosis and prognosis of intracranial teratomas diagnosed in utero, and the association of this tumour with pulmonary hypoplasia, are discussed. Originally published Journal of Medical Genetics, Vol. 30, No. 10, Oct 1993
Keywords: Intracranial tumor; Teratoma; Pulmonary hypoplasia